On the Strong Solution for the 3D Stochastic Leray-Alpha Model. (2nd February 2010) - Deugoue, Gabriel; Sango, Mamadou
Abstract : We prove the existence and uniqueness of strong solution to the stochastic Leray-α equations under appropriate conditions on the data. This is achieved by means of the Galerkin approximation scheme. We also study the asymptotic behaviour of the strong solution as alpha goes to zero. We show that a sequence of strong solutions converges in appropriate topologies to weak solutions of the 3D stochastic Navier-Stokes equations.